OPTIMIZATION OF ORGANIC LOADING RATE AND HYDRAULIC RETENTION TIME FOR MAXIMUM PRODUCTION OF METHANE THROUGH ANAEROBIC CO-DIGESTION OF CANOLA STRAW AND BUFFALO DUNG - A. R. Sahito; R. B. Mahar; F. Ahmed (Journal of Animal and Plant Sciences, 2016)
In more than a few regions of Pakistan, crop residues are being wasted and are leading to a solid waste problem. Anaerobic co-digestion of crop residues along with animal dung is one of the appropriate method to convert wasted crop residues into the renewable energy. In the present study, the anaerobic co-digestion of canola straw long with buffalo dung was carried out in continuously stirred tank reactor (CSTR) for optimization of organic loading rate (OLR) and hydraulic retention time (HRT). The various organic loads were added in the range of 2-4 gVS L-1day-1, whereas various HRTs were kept from 20-35 days. Results reveal that on the increase of the OLR, the volumetric methane production increases, without significantly compromising methane yield. On the contrary, by increasing the HRT, the volumetric methane production decreases, whereas the specific methane production increases. The optimum OLR and HRT were observed as 2.66 gVS L-1day-1 and 30 days respectively, where maximum specific methane production was observed as 143 NmL g-1VSadded. Moreover, the experimental data were simulated, which reveals that and the reaction kinetic follow the first order CSTR model efficiently.
Keywords: optimization; hydraulic retention time; organic loading rate; canola straw; buffalo dung